Penerapan Konseling Behavior Untuk Mengurangi Kecenderungan Perilaku Konsumtif Mahasiswa Psikologi 2018 UIN Malang - Ulya, Rifqi Minchatul; El Hakim, Ahmad Fahmi Idris; Jamaluddin, Muhammad (Konseling Edukasi : Journal of Guidance and Counseling, 2021)
Implementation of Behavior Counseling to Reduce the Tendency of Consumptive Behavior in 2018 Psychology College Students UIN Malang. This study aims to reveal the application of behavioral counseling to reduce the tendency of consumptive behavior in psychology students at UIN Malang. This research on the application of behavioral counseling to reduce the tendency of consumptive behavior was carried out using a pre-experimental design in the form of a one group pretest-posttest design. To measure the level of consumptive behavior, it is done using a consumptive behavior scale which has previously been tested for validity (V 0.87) and reliability (r > 0.80). Analysis of the data using the Wilcoxon test, the results of the study obtained Zcount > Ztable or 2,670 > 1,645 (p < 0.05), meaning that Ha was accepted and Ho was rejected. Thus, the results of the study indicate that it can be said that the application of behavioral counseling can reduce the level of consumptive behavior in psychology students from the 2018 UIN Malang class. Suggestions for further researchers who take the same variables can fill in the blanks from other angles such as focusing on indicators of interest and opinions that have not decreased significantly, or other problematic variables.. Keywords : Consumptive Behavior, Counseling Behavior, College Student